Travel time, availability of emergency obstetric care, and perceived quality of care associated with maternal healthcare utilisation in Afghanistan: A multilevel analysis. Issue 4 (3rd April 2022) - Kim, Christine; Tappis, Hannah; Natiq, Laila; Fried, Bruce; Lich, Kristen Hassmiller; Delamater, Paul L.; Weinberger, Morris; Trogdon, Justin G.
ABSTRACT: Limited understanding of factors such as travel time, availability of emergency obstetric care (EmOC), and satisfaction/perceived quality of care on the utilisation of maternal health services exists in fragile and conflict-affect settings. We examined these key factors on three utilisation outcomes: at least one skilled antenatal care (ANC) visit, in-facility delivery, and bypassing the nearest public facility for childbirth in Afghanistan from 2010 to 2015. We used three-level multilevel mixed effects logistic regression models to assess the relationships between women's and their nearest public facilities' characteristics and outcomes. The nearest facility score for satisfaction/perceived quality was associated with having at least one skilled ANC visit (AOR: 2.02, 95% CI: 1.21, 3.36). Women whose nearest facility provided EmOC had a higher odds of in-facility childbirth compared to women whose nearest facility did not (AOR: 1.24, 95% CI: 1.04, 1.48). Nearest hospital travel time (AOR: 0.95, 95% CI: 0.93, 0.98) and nearest facility satisfaction/perceived quality (AOR: 0.34, 95% CI: 0.14, 0.82) were associated with lower odds of women bypassing their nearest facility. Afghanistan has made progress in expanding access to maternal healthcare services during the ongoing conflict. Addressing key barriers is essential to ensure that women have access to life-saving services.